2015
DOI: 10.1007/s10753-015-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin-3 Attenuates Renal Damage in Diabetic Nephropathy by Promoting M2 Macrophage Differentiation

Abstract: As one of the most important long-term complications of diabetes, diabetic nephropathy (DN) is the major cause of end-stage renal disease and high mortality in diabetic patients. The long pentraxin 3 (Ptx3) is a member of a superfamily of conserved proteins characterized by a cyclic multimeric structure and a conserved C-terminal domain. Several clinical investigations have demonstrated that elevated plasma Ptx3 levels are associated with cardiovascular and chronic kidney diseases (CKD). However, the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
(34 reference statements)
2
33
0
Order By: Relevance
“…Similarly, pentraxin-3 polarized macrophages to an M2 phenotype and ameliorated experimental diabetic renal injury (39). In addition, suppression of renal M1 macrophages by deletion of Toll-like receptors 2 or 4 also protected against development of DN in mice (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pentraxin-3 polarized macrophages to an M2 phenotype and ameliorated experimental diabetic renal injury (39). In addition, suppression of renal M1 macrophages by deletion of Toll-like receptors 2 or 4 also protected against development of DN in mice (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…But at the same time it has been shown that diabetic vascular complications apart from DR also affect the serum levels of PTX3 protein. [38][39][40] Another limitation of our study was its relatively small sample size. It was because of PTX3 levels might be affected by several systemic diseases such as cardiovascular or cerebrovascular diseases, chronic kidney and liver failure, autoimmune disorders, irregular systemic hypertension.…”
Section: Eyementioning
confidence: 98%
“…Recent studies have shown the protective role of PTX3 in nephropathy. PTX3 attenuated renal damage in mice with DN by promoting M2 macrophage differentiation 10. Therefore, it is hypothesized that PTX3 may be involved in the pathogenesis of DN development.…”
Section: Introductionmentioning
confidence: 99%